FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PENAMBANG GALIAN GOLONGAN C DI KECAMATAN ANGGALOMOARE KABUPATEN KONAWE PROVINSI SULAWESI TENGGARA - L, Hasrani; Tamburaka, Irmawatty P.; Dja'wa, Asrianti (Jurnal Ekonomi Pembangunan (JEP) UHO, 2023)
This study aims to determine and analyze the effect of capital, working hours and labor on the income of class C mining miners in Anggalomoare District, Konawe Regency, Southeast Sulawesi Province. The population in this study were the owners of the sand mining business units in the Anggalomoare District, amounting to 15 people, the sampling in this study used the census method. The analytical method used in this research is multiple linear regression analysis method. The type of data used is primary data obtained during observations, interviews, questionnaires and secondary data obtained from the Central Statistics Agency. The results of this study indicate that simultaneously the variables of capital (x3), working hours (x2) and labor (x3) have a positive and significant effect, while partially the variables of capital have a positive and significant effect, the working hours variable has a negative and significant effect, the labor variable has a positive and insignificant.